Momentum and the Cross-Section of Stock Volatility - Minyou Fan; Fearghal Kearney; Youwei Li; Jiadong Liu (Queen's University Belfast, Queen's Management School, 2020)
Recent literature shows that momentum strategies exhibit significant downside risks over certain periods, or called "momentum crashes." We find that the high uncertainty of momentum strategies is sourced from the cross-sectional volatility of individual stocks. Stocks with high realised volatility over the formation period tend to lose momentum effect, while stocks with low realised volatility show strong momentum. A new approach, generalised risk-adjusted momentum (GRJMOM), is introduced to mitigate the negative impact of high momentum risks. GRJMOM is proven to be more profitable and less risky than the existing momentum ranking approaches in multiple asset classes, including the UK stock, commodity, global equity index, and fixed income markets
Keywords: G11; G12; G13; 330